2020
DOI: 10.1016/j.euf.2019.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Mirabegron Add-on Therapy to Tamsulosin for the Treatment of Overactive Bladder in Men with Lower Urinary Tract Symptoms: A Randomized, Placebo-controlled Study (MATCH)

Abstract: Background: Men with lower urinary tract symptoms (LUTS) treated with a-blockers (eg, tamsulosin) may experience overactive bladder (OAB) symptoms and receive add-on antimuscarinics. Mirabegron (a b3-adrenoreceptor agonist) is an alternative add-on therapy. Objective: To evaluate the efficacy of mirabegron versus placebo in men with OAB symptoms receiving tamsulosin for LUTS. Design, setting, and participants: Japanese and Korean men with OAB treated with tamsulosin for LUTS (January 2016-July 2017). Intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
61
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 35 publications
9
61
2
2
Order By: Relevance
“…previous studies that found the majority of TEAEs were mild or moderate following TAM + MIRA treatment. 19,23 Furthermore, similar low incidences of serious TEAEs were reported in both PLUS (2.8%) and in MATCH (2.1%) following TAM + MIRA treatment. 19 No deaths were reported in either study, which comprised 1283 randomized patients overall.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…previous studies that found the majority of TEAEs were mild or moderate following TAM + MIRA treatment. 19,23 Furthermore, similar low incidences of serious TEAEs were reported in both PLUS (2.8%) and in MATCH (2.1%) following TAM + MIRA treatment. 19 No deaths were reported in either study, which comprised 1283 randomized patients overall.…”
Section: Discussionsupporting
confidence: 69%
“…19,23 Furthermore, similar low incidences of serious TEAEs were reported in both PLUS (2.8%) and in MATCH (2.1%) following TAM + MIRA treatment. 19 No deaths were reported in either study, which comprised 1283 randomized patients overall. In PLUS, a low proportion of TAM + MIRA patients experienced a TEAE that caused the patient to discontinue from the study.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations